2002
DOI: 10.1093/jxb/erf079
|View full text |Cite
|
Sign up to set email alerts
|

Salt-stress-induced ABA accumulation is more sensitively triggered in roots than in shoots

Abstract: Salt-stress-induced ABA accumulation in maize root tissues was compared with that in leaf tissues. While salt stress with NaCl resulted in a significant ABA accumulation in root tissues (up to 10-fold), the same stress only led to a small ABA accumulation in leaf tissues (about 1-fold). Pretreatment with ethylene glycol (EG), a permeable and inert monomer of PEG, could prevent the shrinkage of cell volume and completely block the ABA accumulation in leaf tissues under salt stress, but substantial salt-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
116
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(129 citation statements)
references
References 28 publications
12
116
0
1
Order By: Relevance
“…When shoots were cultured 503 in vitro, no accumulations of ABA were observed in any of 504 the studied genotypes, which seem to discard an ABA 505 dependent signaling. These results are similar to those 506 obtained in maize by Jia et al (2002), who observed that 507 NaCl treatment only induced a small ABA accumulation in 508 leaf tissues, whereas on the contrary, the same treatment of 509 NaCl caused a significant ABA accumulation in root 510 tissues.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…When shoots were cultured 503 in vitro, no accumulations of ABA were observed in any of 504 the studied genotypes, which seem to discard an ABA 505 dependent signaling. These results are similar to those 506 obtained in maize by Jia et al (2002), who observed that 507 NaCl treatment only induced a small ABA accumulation in 508 leaf tissues, whereas on the contrary, the same treatment of 509 NaCl caused a significant ABA accumulation in root 510 tissues.…”
supporting
confidence: 86%
“…These 498 results suggested the existence of an osmosensing mecha-499 nism and also the organ-specific nature of such a response. 500 This suggestion is also supported by the fact that gene 501 expression in response to salt stress usually is organ-or 502 tissue-specific (Jia et al 2002). When shoots were cultured 503 in vitro, no accumulations of ABA were observed in any of 504 the studied genotypes, which seem to discard an ABA 505 dependent signaling.…”
mentioning
confidence: 91%
“…Root growth is significantly affected by environmental stimuli. Salinity and water stress induce ABA accumulation in roots (Zhang and Davies, 1987;Jia et al, 2002). The involvement of ABA in root development under water deficit conditions has also been examined (Sharp and LeNoble, 2002;Sharp et al, 2004).…”
mentioning
confidence: 99%
“…The SOS3 activates SOS2, a protein kinase to be/thr. Salinity induces the biosynthesis and accumulation of the stress hormone in plants, the ABA (Jia et al 2002) and also induces accumulation of ROS (Hernandez et al, 2001). The ROS-mediated signaling under salt stress, occurs through the mitogen-activated protein kinases (MAPKs) (Pei et al 2000).…”
Section: Salt Stressmentioning
confidence: 99%